Empirical Exploration of Optimal Gating System Design for Sand Casting Process (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This paper aims to analyse and optimise the gating system used in the sand casting process to produce drainage doors at Deepshikha Casting in Nagpur. It focuses on understanding how gate design impacts productivity and the quality of the cast, drawing attention to common defects and the role of gravity casting techniques.Design/Methodology/Approach: This paper discusses the present gating system of Deepshikha Casting in detail to identify defects, such as sand inclusions, blow holes, pinholes, gas holes, shrinkage, and misruns. The present gating ratio and system weight assessment are thus used to suggest changes in the design to improve the process efficiency and quality of the product.Findings: The research indicates that the existing gating system has an inappropriate gating ratio, resulting in a high rate of faults and reduced productivity. The system also weighs a lot, which deters efficiency. Improving the gating design reduces flaws, increases the quality of castings, and enhances molten metal flow.Research Limitation: The output of the present work is limited to Deepshikha Casting alone, which is used for drainage door casting. Further research must be conducted on different casting products and technologies for a broad application.Practical Implication: This sector of sand casting can benefit from optimising the gating system, maximising productivity and minimising casting defects, thus reducing costs and improving efficiency.Social Implication: The environment will also benefit from efficient casting because of reduced use of resources, reduced waste, and fewer consumables. Better procedures also translate to increased production of safer products.Originality/Value: This paper provides practical, applied solutions for optimising the gating system of sand casting. Its insights are particularly informative for a foundry working with fragile metals and using gravity casting.
Keywords: Casting. gating scheme. gravity. mould cavity. productivity